Penerapan Metode Dempster Shafer Dalam Mendiagnosa Penyakit Tumor Hipofisis - Roberto Valentinus Manurung; Muhammad Syahrizal; Murdani Murdani (Building of Informatics, Technology and Science (BITS), 2021)
Pituitary tumors are relatively common intracellular neoplasms, and constitute 10-15% of all intracial neoplasms. These types of tumors often have difficulties and not infrequent recurrence, even though surgery has been done. Although there have been many studies on pituitary tumors, the pathogenesis of the occurrence of these tumors is not entirely clear. It is generally considered that pituitary neoplasms are primary pituitary tumors. Biomolecular electrons show that pituitary tumors, both functional and non-functional, originate from the growth of one clone (monoclonal). The Dempster-Shafer method is used to look for inconsistencies in effects and also new facts that will change existing attitudes, using the Dempster-Shafer method that allows a person to be safe in the work of an expert. This study aims to apply the Dempster-Shafer method to expert systems to diagnose the risk level of a person's pituitary tumor based on factors and symptoms of a pituitary tumor. The problem experienced by the community is the difficulty of specialist pituitary tumors due to the limited time of specialists to work, besides that in terms of very expensive costs for them or those whose economies cannot diagnose or consult with tumor specialists.